2015
DOI: 10.1074/jbc.m115.657486
|View full text |Cite
|
Sign up to set email alerts
|

Expression of V3 Versican by Rat Arterial Smooth Muscle Cells Promotes Differentiated and Anti-inflammatory Phenotypes

Abstract: Background: Arterial smooth muscle cells (ASMCs) undergo phenotypic changes during pathophysiological processes. Results: V3 expression increases contractile SMC markers while decreasing a broad range of proinflammatory chemokines and transcription factors. Conclusion: V3 expression reprograms rat ASMCs promoting differentiated and anti-inflammatory phenotypes. Significance: Modifying ECM components via V3 expression could provide a potential therapeutic intervention against vascular and other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 69 publications
1
21
0
1
Order By: Relevance
“…In addition, we showed that manipulating the expression of versican by overexpressing the V3 isoform in experimentallyinduced atherosclerotic lesions in rabbits significantly reduced macrophage infiltration, inhibiting the development of lipidfilled atherosclerotic lesions (84). Furthermore, our in vitro studies using rat arterial smooth muscle cells demonstrated that the V3 expression effect is anti-inflammatory and decreased the expression of the CS-containing versican isoforms, V0 and V1, and the formation of elastic fibers which are a poor substrate for macrophages (42,43). Such results further support a critical role for versican in myeloid cell accumulation in atherosclerosis and perhaps in other diseases as well (39).…”
Section: Versican: Interplay With Leukocytesmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, we showed that manipulating the expression of versican by overexpressing the V3 isoform in experimentallyinduced atherosclerotic lesions in rabbits significantly reduced macrophage infiltration, inhibiting the development of lipidfilled atherosclerotic lesions (84). Furthermore, our in vitro studies using rat arterial smooth muscle cells demonstrated that the V3 expression effect is anti-inflammatory and decreased the expression of the CS-containing versican isoforms, V0 and V1, and the formation of elastic fibers which are a poor substrate for macrophages (42,43). Such results further support a critical role for versican in myeloid cell accumulation in atherosclerosis and perhaps in other diseases as well (39).…”
Section: Versican: Interplay With Leukocytesmentioning
confidence: 71%
“…Interestingly, the different isoforms exhibit functional differences regarding their impact on cell phenotype, such as the ability of V1 to promote proliferation and inhibit apoptosis, while V2 exhibits antiproliferative activity (37,38). In contrast, V3 regulates ECM assembly and inhibits cell proliferation and migration (39)(40)(41)(42)(43)(44)(45). A new V5 isoform has been recently described and shown to be expressed by injured rat neurons (46).…”
Section: Versicanmentioning
confidence: 99%
“…34, 35 Versican staining was significantly increased in AscA and AA at both 4 and 14 weeks (4 – 47-fold, P < 0.001). Versican staining was typically highest in regions with PAU and adjacent Mac-2 staining (Figure XIV in the online-only Data Supplement).…”
Section: Resultsmentioning
confidence: 96%
“…Originally published as Figure 11 Intriguingly, overexpression of the V3 spliced variant of versican lacking GAG-binding regions has been demonstrated to retard inflammatory cytokine production (including CXCL1, CCL20, CCL2) in smooth muscle cells via blockade of epidermal growth factor receptor and NFκB signaling cascades. 140,141 Overexpression of V3 in melanoma cells reduces the rate of tumor growth by decreasing the proliferative index and increasing the apoptotic rate of primary tumor cells. [142][143][144] In addition, expression of a mutant G3ΔEGF construct (the versican G3 domain with deletion of the EGF-like repeats) also results in slower growth, increased apoptotic rate, and lower tumorigenic potential of astrocytoma cells.…”
Section: Versican As a Regulator Of Pulmonary Innate Immunementioning
confidence: 99%